Effect of CT Specimen Geometry to Fracture Properties of Aluminium Alloy Using Simulation Analysis - ZAWAWI, NORASMA SALSABILA; ABDUL LATIF, NORADILA (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Aluminum alloys are the alloys in which aluminium is present as the predominant metal. Due to its strength and fracture, aluminium alloys are widely used in aviation, aerospace, energy, transportation, and automotive industries. This study was conducted to identify the mechanical properties of aluminium alloys in simulation analysis and compare the data obtained with the previous research. The variation of plastic behavior on different types of the specimen was conducted to study which specimen will give a better result in terms of its strength and chemical composition contains in aluminium alloys. There were several samples made by Al7075, Al7075-T6 and Al6061-T6 used and three different loads were applied to start from 2500 N, 3750 N, and 5000 N. As the load applied to the specimens increased, the stress will also increase for the specimens to withstand the load applied. There is a linear relationship between stress-load, stress-deformation, and stress-strain graphs. Yield strength can be obtained from the stress-strain graph. Based on the results, 0.187 W CT specimen shows the strongest tensile strength when compared with other specimens tested. In term of material properties, all of the specimens indicates the highest results of yield strength in Al6061-T6 compared to other two materials. These results were affected by the chemical composition of aluminium alloys, the specimen configuration, and the plastic zone size.